2013
DOI: 10.1128/jcm.02443-12
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Interspersed Repetitive-Unit–Variable-Number Tandem-Repeat (MIRU-VNTR) Genotyping of Mycobacterium intracellulare for Strain Comparison with Establishment of a PCR-Based Database

Abstract: Strain comparison is important to population genetics and to evaluate relapses in patients with Mycobacterium avium complex (MAC) lung disease, but the "gold standard" of pulsed-field gel electrophoresis (PFGE) is time-consuming and complex. We used variable-number tandem repeats (VNTR) for fingerprinting of respiratory isolates of M. intracellulare from patients with underlying bronchiectasis, to establish a nonsequence-based database for population analysis. Different genotypes identified by PFGE underwent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…Studies have shown the ability of VNTR analysis to meet the criteria for discrimination from the closely related species M. intracellulare (11)(12)(13), and preliminary studies have shown VNTR analysis to be feasible with M. avium (8,9). Thus, we undertook a study on the use of VNTR analysis in the clinical setting of U.S. patients with nodular bronchiectasis and M. avium.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown the ability of VNTR analysis to meet the criteria for discrimination from the closely related species M. intracellulare (11)(12)(13), and preliminary studies have shown VNTR analysis to be feasible with M. avium (8,9). Thus, we undertook a study on the use of VNTR analysis in the clinical setting of U.S. patients with nodular bronchiectasis and M. avium.…”
Section: Methodsmentioning
confidence: 99%
“…For patients with suspected microbiological relapse, current isolates were compared to previous isolates stored at Ϫ70°C or stored in their original broth culture vials at room temperature following primary isolation. Sputum cultures from patients had been submitted to and processed by the clinical mycobacteriology laboratory as described previously (3,4,12). Sputum isolates from three recent studies (20; R. J. Wallace, Jr., unpublished data) comparing patient and household water MAC isolates (5) were also included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations